Concept of enhanced frequency chirping for multi-pass cells to improve the pulse contrast - Benner, Maximilian; Karst, Maximilian; Mendez, Cristina Amaya; Stark, Henning; Limpert, Jens (Journal of the Optical Society of America B-Optical Physics, 2023)
The technique of enhanced frequency chirping can be implemented in multi-pass cells to significantly improve the temporal contrast without a penalty in efficiency. In contrast to waveguides, multi-pass cells offer the unique opportunity to tailor the nonlinear interaction, as spectral broadening and dispersion can mostly be spatially separated. By including additional dispersion through the multi-pass cell mirrors, the pulse form can be controlled, which leads to a decrease of the spectral modulations. A pulse possessing this smoother spectrum can be compressed to reach higher peak powers and have more energy in the main feature compared to classical multi-pass cells.
CRIS-Team Scopus Importer:2023-04-20